Inteligência Artificial e Automação: Impactos na Economia e no Emprego - Almeida, E. C. (2024 Angola Annual Summit, 2024)
In this presentation/talk, an overview will be provided of what is understood by the Digital Revolution, exploring what it is and how it can influence productive efficiency through Artificial Intelligence and Automation. It will also address the challenges and opportunities presented to the labor market, as well as the specific challenges and opportunities that Angola, in particular, and Africa, in general, can derive from these new technologies.